Artificial Intelligence Anxiety of Family Physicians in Turkey - Baser, Aysel; Baktır Altuntaş, Sibel; Kolcu, Giray; Özceylan, Gökmen (Progress in Nutrition, 2021)
Study Objectives: Artificial intelligence (AI) is a computer system or a robot under the control of this system performing tasks similar to humans. In this study, it was aimed to evaluate the artificial intelligence anxiety of family physicians in Turkey. Method: Artificial Intelligence Anxiety Scale, which was developed by Wang, which Turkish validity and reliability study was conducted by Terzi, was preferred as the data collection tool. The universe was identified as Family Physician in Turkey (N=23,992). The sample size was calculated as 378 (n=378), regional populations were stratified according to gender and age groups. Results: Within the scope of the study, Family Physicians / Family Medicine Specialists were included in the study (n.402). In evaluating the scale scores, the mean total score was 76.30±27.87, the learning sub-dimension average score was 24.83±11.46, the job change sub-dimension mean score was 21.51±8.68, and the sociotechnical subscale mean score was 18.95±6.44. The mean score of the artificial intelligence configuration sub-dimension was 6.44, and 10.99 ± 5.96. Conclusions: Since most physicians have not received training on AI applications and their anxiety levels are low, we believe that structured training programs and artificial intelligence applications in family medicine can be integrated into decision support systems and contribute to patient safety.